Accessory minerals to U, Th, REE in sandstones and conglomerates of Archean Pongola Basin (South Africa) - (:unkn) unknown (My University, 2015)
In South Africa, the Pongola Supergroup was deposited on the craton Kaapvaal about 3 Ga years. The Mozaan group based on the basal Nsuze group and contains mudstones, arenites, sandstones and conglomerates. In this type of conglomerate, uranium and gold mineralization deposits have been recognized in the world, Canada, Brazil, Australia and South Africa. Small mineralization have been proved to in the Mozaan group, very different from those that have been exploited in the the neighbor of the Witwatersrand Basin. The petrographic, mineralogical and geochemical work concerns basal conglomerate and sandstone formations of Mozaan Group in Denny Dalton. It is based on the study of two cores where uranium mineralizations have been recognized. Particular attention was focused on the detrital material, because in these conglomerates, the deposits are placer type with the remobilizations more or less marked. The detrital grains identified associated with the detrital pyrite are frequent monazite, titanium oxides, thorium uranium minerals (coffinite, thorite, and thorianite), zircon, apatite, chromite and other sulphides (chalcopyrite, arsenopyrite). The source rock is likely acidic material with low basic contribution and metamorphic.The mineral morphology suggests a short transport the source to the Pongola basin. Petrographic and chemical analyzes show that characterize the different diagenetic mineralization and hydrothermal processes that have affected the Mozaan group. New observations were made on uranium minerals with the detection of phospho-coffinite, aluminous hydrated rare earth phosphates and highly developed alterations affecting monazite grains. These mineral assemblages reveal a diagenesis with the flow of acidic fluids as evidenced by the presence of pyrite and APS in the secondary porosity of the rocks. Detrital and authigène uraninite grains were not observed in this study. The most likely hypothesis is that the uranium mineralized zones come
Keywords: African Research